Fetal cerebellar growth and Sylvian fissure maturation: international standards from Fetal Growth Longitudinal Study of INTERGROWTH‐21st Project. (1st April 2021) - Rodriguez‐Sibaja, M. J.; Villar, J.; Ohuma, E. O.; Napolitano, R.; Heyl, S.; Carvalho, M.; Jaffer, Y. A.; Noble, J. A.; Oberto, M.; Purwar, M.; Pang, R.; Cheikh Ismail, L.; et al.
ABSTRACT: Objective: To construct international ultrasound‐based standards for fetal cerebellar growth and Sylvian fissure maturation. Methods: Healthy, well nourished pregnant women, enrolled at < 14 weeks' gestation in the Fetal Growth Longitudinal Study (FGLS) of INTERGROWTH‐21 st, an international multicenter, population‐based project, underwent serial three‐dimensional (3D) fetal ultrasound scans every 5 ± 1 weeks until delivery in study sites located in Brazil, India, Italy, Kenya and the UK. In the present analysis, only those fetuses that underwent developmental assessment at 2 years of age were included. We measured the transcerebellar diameter and assessed Sylvian fissure maturation using two‐dimensional ultrasound images extracted from available 3D fetal head volumes. The appropriateness of pooling data from the five sites was assessed using variance component analysis and standardized site differences. For each Sylvian fissure maturation score (left or right side), mean gestational age and 95% CI were calculated. Transcerebellar diameter was modeled using fractional polynomial regression, and goodness of fit was assessed. Results: Of those children in the original FGLS cohort who had developmental assessment at 2 years of age, 1130 also had an available 3D ultrasound fetal head volume. The sociodemographic characteristics and pregnancy/perinatal outcomes of the study sample confirmed the health and low‐risk status of the population studied. In addition, the fetuses had low morbidity and adequate growth and development at 2 years of age. In total, 3016 and 2359 individual volumes were available for transcerebellar‐diameter and Sylvian‐fissure analysis, respectively. Variance component analysis and standardized site differences showed that the five study populations were sufficiently similar on the basis of predefined criteria for the data to be pooled to produce international standards. A second‐degree fractional polynomial provided the best fit for modeling transcerebellar diameter; we then estimated gestational‐age‐specific 3 rd, 50 th and 97 th smoothed centiles. Goodness‐of‐fit analysis comparing empirical centiles with smoothed centile curves showed good agreement. The Sylvian fissure increased in maturation with advancing gestation, with complete overlap of the mean gestational age and 95% CIs between the sexes for each development score. No differences in Sylvian fissure maturation between the right and left hemispheres were observed. Conclusion: We present, for the first time, international standards for fetal cerebellar growth and Sylvian fissure maturation throughout pregnancy based on a healthy fetal population that exhibited adequate growth and development at 2 years of age. © 2020 The Authors. Ultrasound in Obstetrics & Gynecology published by John Wiley & Sons Ltd on behalf of International Society of Ultrasound in Obstetrics and Gynecology.